Short QRS Duration After His-Purkinje Conduction System Pacing Predicts Left Ventricular Complete Reverse Remodeling in Patients With True Left Bundle Branch Block and Heart Failure - Guan, Xu-Min; Li, Dan-Na; Zhao, Fu-Lu; Zhao, Yan-Ni; Yang, Yi-Heng; Dai, Bai-Ling; Dai, Shi-Yu; Gao, Lian-Jun; Xia, Yun-Long; Dong, Ying-Xue (Frontiers in Cardiovascular Medicine, 2022)
Objective This study aimed to explore the outcomes of His-Purkinje conduction system pacing (HPCSP) and to screen the predictors of left ventricular (LV) complete reverse remodeling in patients with true left bundle branch block (LBBB) and heart failure with reduced ejection fraction (HFrEF). Methods Patients who underwent HPCSP for true LBBB and HFrEF from April 2018 to August 2020 were consecutively enrolled. All participants were followed up for at least 1 year. Thrombosis, infection, lead dislodgement, perforation, and other complications were observed after HPCSP. Clinical data, including echocardiographic parameters, electrocardiogram measurements, and cardiac function, were assessed before and after the procedure. Results A total of 46 patients were enrolled. HPCSP was successfully deployed in 42 cases (91.30%), which included 37 cases with His bundle pacing (HBP) and 5 cases with left bundle branch pacing (LBBP). The QRS duration decreased significantly (169.88 ± 19.17 ms vs. 113.67 ± 20.68 ms, P < 0.001). Left ventricular end-systolic volume (LVESV) (167.67 ± 73.20 ml vs. 85.97 ± 62.24 ml, P < 0.001), left ventricular end-diastolic diameter (LVEDD) (63.57 ± 8.19 mm vs. 55.46 ± 9.63 mm, P = 0.003) and left ventricular ejection fraction (LVEF) (26.52 ± 5.60% vs. 41.86 ± 11.56%, P < 0.001) improved dramatically. Complete reverse remodeling of the LV with normalized LVEF and LVEDD was found in nearly half of the patients (45.24%). A short QRS duration after HPCSP was a strong predictor of normalized LVEF and LVEDD (P < 0.001). The thresholds increased markedly in two patients approximately 6 months after HBP. No patients died during the total follow-up period of 20.07 ± 6.45 months. Conclusion Complete reverse remodeling of the LV could be found in nearly half of the patients with HFrEF and true LBBB after HPCSP, and the short QRS duration after HPCSP was a strong predictor.